(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
In an era where governments and organisations dedicated to improving education worldwide are concerned about quality teacher education and dominate the national discourse, it is crucial to emphasise teacher quality, gender parity, satisfaction, and commitment. This article examines the role of gender as a moderator between tutor job satisfaction and organisational commitment in Ghanaian Colleges of Education. A research hypothesis was formulated with a cross-sectional survey to guide the study. A sample of 319 tutors was used. Multivariate multiple regression, SEM and Process Analysis were used to test the hypothesis. The study revealed that gender was a significant moderator between job satisfaction and organisational commitment of tutors in Ghana. As a result of this, it was recommended that the governing council focus on factors affecting the extrinsic and intrinsic motivations (job satisfaction) of their tutors so that stronger commitment and greater loyalty may be demonstrated by the tutors.